Understanding the self - Frando, Milagros F.; Arceno-Isip, Lalaine (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2019)
Understanding the self is one of the courses offered in the tertiary level mainly because of the fact that it is part of the liberal education. Etymologically, the term "liberal" comes from the Latin word "libre" which means free. Simply defined, liberal education pertains to an education that liberates (or frees) oneself from ignorance and prejudices.
Part I - The Various selves -- Chapter 1 : Building identity : The Construction of the self -- Chapter 2 : Building identity : The Social self -- Chapter 3 : Building identity : the Self embedded in culture -- Chapter 4 : Building identity : The Psychological construction of the self -- Part II - Discovering the self -- Chapter 5 : Discovering the self : The Physical self -- Chapter 6 : Discovering the self : The Sexual self -- Chapter 7 : Discovering the self : The Material/economic self -- Chapter 8 : Discovering the self : The Spiritual self -- Chapter 9 : Discovering the self : The Political self -- Chapter 10 : Discovering the self : The Digital self -- Part 3 - Learning and caring for the self -- Chapter 11 : Learning and caring for self : the Better learner -- Chapter 12 : Learning and caring for the self : Goal settings -- Chapter 13 : Learning and caring for the self : taking charge of one's health -- Chapter 14 : The Filipino identity : The Filipino's sense of the self.
Includes bibliographical references.
Keywords: PSYCHOLOGY